The protection of personal data and the right to be forgotten in Peru. On the purpose of the international standards of the Inter-American Human Rights system - Franco García, Devora (2020)
In 2014, the Court of Justice of the European Union recognized the right to be forgotten based on the interpretation of a regulatory framework related to the protection of personal data. Over time, many Latin American countries, including Peru, have enacted laws regulating the processing of personal data. The Directorate for the Protection of Personal Data of Peru, from the entry into force of Law N° 29733, Protection of Personal Data Law, has recognized the exercise of the right to be forgotten and has ordered the de-indexing from search engine content. On the other hand, in the Inter-American Human Rights System, through the Office of the Special Rapporteur for Freedom of Expression, this right has been rejected. This is because, as it has been conceived in the European system, freedom of expression would be illegitimately restricted. This article aims to analyze the content of the right to be forgotten, as well as the limitations that must be observed at the time of recognition. Likewise, the challenges faced by this right in the Peruvian regulatory system will be evidenced, considering the criteria adopted by the Constitutional Court of Peru, as well as those adopted within the Inter-American Human Rights System.